2021
DOI: 10.1039/d0dt03906c
|View full text |Cite
|
Sign up to set email alerts
|

A weakly luminescent Tb-MOF-based “turn-on” sensor for the highly selective and sensitive sensing of an anthrax biomarker

Abstract: A weakly luminescent Tb-MOF-based “turn-on” sensor for the highly selective and sensitive sensing of an anthrax biomarker was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The results indicated that the peak positions of the Zn-MOF hardly change except for those at pH = 14 and pH = 1, demonstrating its excellent acid–base stability. 47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the peak positions of the Zn-MOF hardly change except for those at pH = 14 and pH = 1, demonstrating its excellent acid–base stability. 47…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the peak positions of the Zn-MOF hardly change except for those at pH = 14 and pH = 1, demonstrating its excellent acid-base stability. 47 The IR spectra of the Zn-MOF and ligands were also recorded to confirm its structure (Fig. S3 †).…”
Section: Pxrd and Ir Analysismentioning
confidence: 99%
“…[ 30–32 ] Especially, Eu/Tb‐CPs with narrow and typical luminescence emissions have been widely used as luminescence sensors for the detection of different analytes including metal ions, anions, and organic small molecules. [ 20–25 ] Moreover, for sensing practical applications, most of cases are working in water systems; thus, the design and synthesis of Ln‐CPs with high water stability are of great importance. In order to achieve this purpose, most of Ln‐CPs were constructed by conjugated aromatic carboxylate ligands with different potential functional sites, which can have interaction with analytes, thus leading to the change of luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, latter ligands including 1,10-phenanthrolin and 2,2′-bipyridine can form only chelate rings with metal ions thus preventing the formation of high dimensional frameworks so they are also known as terminators. 8 Among O-donor ligands, pyridine-based carboxylate ligands are responsible for creating thousands of compounds known not only for their structural diversity but also for their wide variety of applications in many fields from catalysts, 9,10 luminescence, 11,12 gas adsorption 13,14 to their antiproliferative activities. 15,16 For several years, pyridine-2,6dicarboxylic acid (H 2 pydco) has received considerable attention due to the symmetric position of its carboxylate groups on each side of the pyridine ring which can form 5-membered chelate rings or bridge with neighboring metal centres.…”
Section: Introductionmentioning
confidence: 99%